Community Engagement: A pedagogical model for teaching social justice in Law Schools - Ochieng, Paul; Nzomo, Patrick (Pázmány Law Review, 2025)
This paper explores community engagement as a pedagogical model for teaching social justice in law schools, with a particular focus on Strathmore University in Kenya. Rooted in Catholic social teaching, the university integrates experiential learning into its legal education through service-based learning, community service, and pro bono legal aid. All students at the university, including law students, are required to complete 200 hours of community service. They are further encouraged to participate in the Legal Aid Caravan, one of the many initiatives of the Strathmore Law Clinic, which provides free legal services to marginalised communities. These initiatives enable students to bridge the gap between legal theory and practice while confronting real-world injustices such as land disputes, gender-based violence, and discrimination. The pedagogical model fosters professional skills, including legal research, client care, and leadership, while cultivating moral responsibility, empathy, and a commitment to justice. By engaging with historically underserved populations, students learn to integrate law with moral philosophy, sociology, and economics, thereby deepening their understanding of the rule of law’s contribution to the common good. The article argues that experiential learning through community engagement is vital for shaping ethically conscious lawyers who view law not merely as an instrument, but as a tool for advancing justice and human dignity.